Fennoscandian tree-ring anatomy shows a warmer modern than medieval climate. - Björklund, Jesper; Seftigen, Kristina; Stoffel, Markus; Fonti, Marina V; Kottlow, Sven; Frank, David C; Esper, Jan; Fonti, Patrick; Goosse, Hugues; Grudd, Håkan; Gunnarson, Björn E; Nievergelt, Daniel; et al. (Nature, 2023)
Earth system models and various climate proxy sources indicate global warming is unprecedented during at least the Common Era1. However, tree-ring proxies often estimate temperatures during the Medieval Climate Anomaly (950-1250 CE) that are similar to, or exceed, those recorded for the past century2,3, in contrast to simulation experiments at regional scales4. This not only calls into question the reliability of models and proxies but also contributes to uncertainty in future climate projections5. Here we show that the current climate of the Fennoscandian Peninsula is substantially warmer than that of the medieval period. This highlights the dominant role of anthropogenic forcing in climate warming even at the regional scale, thereby reconciling inconsistencies between reconstructions and model simulations. We used an annually resolved 1,170-year-long tree-ring record that relies exclusively on tracheid anatomical measurements from Pinus sylvestris trees, providing high-fidelity measurements of instrumental temperature variability during the warm season. We therefore call for the construction of more such millennia-long records to further improve our understanding and reduce uncertainties around historical and future climate change at inter-regional and eventually global scales.